King Arthur in antiquity - Anderson, Graham (Routledge, 2004)
Although King Arthur's identity is so frequently debated, he is almost always set somewhere in the Celtic Britain of the Early Christian Era. This original and wide-ranging study argues that the roots of the Arthur legend are to be found in classical antiquity and that the traditional British Arthur is a much later imitation. Graham Anderson examines hitherto neglected evidence for two much older figures, known to classical writers as early kings of Arcadia and Lydia, who supposedly flourished more than a millennium earlier than traditional accounts suggest. He outlines the correspondence betw.